ANGKA KEJADIAN DIPLOPIA PADA PASIEN FRAKTUR MAKSILOFASIAL DI BANGSAL BEDAH RSUD ARIFIN ACHMAD PROPINSI RIAU PERIODE JANUARI 2011 – DESEMBER 2013 - Ni Komang Tri Adrianti; Kuswan Ambar Pamungkas; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDiplopia caused by maxillofacial fracture is diplopia binocular. Diplopia on maxillofacial fractures are one of absolute indications whether the patient will be operated or not, so physician can give the best treatment. This research is aimed to know the incidence of diplopia in patient with maxillofacial fractures at Arifin Achmad General Hospital period January 2011 – December 2013. The type of this research is a descriptive retrospective research. The sample of this research is all of patients with maxillofacial fractures’ medical records at Arifin Achmad General Hospital period January 2011 – December 2013, there are 162 sample included in this research. This research shows that the incidence of diplopia in maxillofacial fracture is 11,1% with the increasing case percentage from 2011 until 2013 (16%  34%  50%). Age group with the most frequent diplopia case is founded in age group between 15 to 24 years old (67%), the majority sex is male (78%). The most frequent type of diplopia is in multiple fractures (94%).Keywords: Diplopia binocular, maxillofacial fracture.